2001
DOI: 10.1128/jcm.39.7.2463-2465.2001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of the babA2 Genotype of Helicobacter pylori in Japanese Clinical Isolates

Abstract: Genotypic variation of Helicobacter pylori is speculated to associate with different clinical outcomes. In Western countries, the gene encoding blood group antigen-binding adhesin (BabA), babA2, is of high clinical relevance and is a useful marker to identify patients who are at higher risk for peptic ulceration and gastric adenocarcinoma, as are vacA and cagA. We investigated the presence of babA2 and cagA in 179 Japanese clinical isolates by PCR and Southern blot analysis and looked for correlations with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
61
5
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 29 publications
8
61
5
5
Order By: Relevance
“…En Japón se reporta una prevalencia de babA2 mucho mayor (84,9%), QUIROGA A.J., CITTELLY D.M., BRAVO M.M. sin asociación significativa entre su presencia y el resultado clínico de la infección (37).…”
Section: Discussionunclassified
“…En Japón se reporta una prevalencia de babA2 mucho mayor (84,9%), QUIROGA A.J., CITTELLY D.M., BRAVO M.M. sin asociación significativa entre su presencia y el resultado clínico de la infección (37).…”
Section: Discussionunclassified
“…Most previous studies evaluating BabA (babA) status have used PCR techniques based on detection of the 10 bp deletion to distinguish between the babA2 and babA1 genes ( Table 2) [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] . However, as described above, strains carrying the prototypical silent babA1 gene are very rare, and in addition, the BabA protein levels often do not match the presence of the babA (babA2) gene [31] .…”
Section: Detection Of Functional Baba Genementioning
confidence: 99%
“…babA status (babA2 positive or negative) was determined by PCR using primer pairs and amplification conditions previously described (Figure 1). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Most of these primers were designed to detect the 10-bp signal sequence deletion of babA1, which is absent in babA2. Most previous studies used primer pair A (babA2S and babA2AS) ( Table 1) in which 2 nucleotides of the forward primer were changed from the known sequences of the babA2 gene from strain CCUG17875 (ie, AC to GT) ( Figure 1).…”
Section: Baba Genotypesmentioning
confidence: 99%
“…24,25 Finally, not all of these PCR-based studies have shown an association between babA2 and intense cellular mucosal inflammations and/ or increased risk of peptic ulcer diseases and gastric cancer (Table 1). [10][11][12][13]19,20,22 Therefore, in the current study, we have compared results from PCR-based strategies that currently are used to predict BabA functional status with those from strategies that measure actual babA expression (ie, immunoblotting) and Le b binding.…”
mentioning
confidence: 99%
See 1 more Smart Citation